Effect of high-dose rosuvastatin loading before percutaneous coronary intervention in Chinese patients with acute coronary syndrome: A systematic review and meta-analysis. - Ziliang Ye; Haili Lu; Qiang Su; Wenqin Guo; Weiran Dai; Hongqing Li; Huafeng Yang; Lang Li (PLoS ONE)
Background Acute coronary syndrome (ACS) is an important disease threatening human life and health. Many studies have shown that the loading dose of atorvastatin can significantly improve the prognosis of patients with ACS, and reduce the mortality. However, this conclusion is not consistent. Thus, we aimed to evaluate the effect of high-dose rosuvastatin loading before percutaneous coronary intervention (PCI) in Chinese patients with ACS using a meta-analysis based on a systematic review of published articles. Methods We systematically reviewed published studies, evaluating the effect of high-dose rosuvastatin loading before percutaneous coronary intervention in Chinese patients with ACS. The retrieval time is limited from inception to 2 November 2016, and the retrieved databases included PubMed, Embase, the Cochrane Library, Web of Science, CBM, CNKI, the VIP database and the Wang Fang database. Two researchers independently assessed the quality of the included studies and then extracted the data. Stata 11.0 was used for data analysis. Results In total, 11 articles, which included 802 patients, were included in our meta-analysis. Among these patients, 398 patients were in the high-dose group (20 mg/day) and 404 patients were in the conventional dose group (10 mg/day). Meta-analysis results showed that compared with the conventional dose group: 1) The loading dose of rosuvastatin can significantly reduce the hs-CRP level after PCI, including at 24 hours (SMD = -0.65, 95%CI -0.84 ~ -0.47, P = 0.000), 48 hours (SMD = -0.40, 95%CI -0.68 ~ -0.11, P = 0.006), and four weeks (SMD = -1.64, 95%CI -2.01 ~ -1.26, P = 0.000). 2) The loading dose of rosuvastatin can significantly reduce the levels of LDL-C and cTnT, including the level of LDL-C at 30 d after PCI (SMD = -0.89, 95%CI -1.10 ~ -0.69, P = 0.000), and the level of cTnT at 24 h after PCI (SMD = -1.93, 95%CI -2.28 ~ -1.59, P = 0.000), and increase the level of HDL-C at 48 h after PCI (SMD = 0.61, 95%CI 0.34 ~ 0.88, P = 0.000). 3) The loading dose of rosuvastatin can significantly reduce the levels of TG and TC, including the level of TG at 30 d after PCI (SMD = -0.94, 95%CI -1.17 ~ -0.71, P = 0.000), the level of TC at 48 h after PCI (SMD = -0.35, 95%CI -0.68 ~ -0.01, P = 0.043), and the level of TC at 30 d after PCI (SMD = -0.77, 95%CI -0.98 ~ -0.56, P = 0.000). Conclusions Our systematic review and meta-analysis showed that, compared with the conventional dose, the loading dose of rosuvastatin was more beneficial to patients with ACS in China and is suitable for clinical application. Due to the limitations of the quality and quantity of included articles, this conclusion still needs to be confirmed by multicenter clinical trials.